Forest fires and carbon emission release in semi-arid regions of Indonesia: the evidence from medium resolution of satellite imagery. Issue 1 (January 2021) - Armanto, AN; Perdinan,; Dasanto, BD; Hidayati, R
Abstract: Forest fires are one of the causes of forest degradation and deforestation in Indonesia. Tropical savanna forests are one of the forest ecosystems found in the Indonesian region with a semi-arid climate type prone to drought and fire. Forest fires contribute to the release of greenhouse gas emissions into the atmosphere. The calculation method to estimate the burnt area is still an obstacle in calculating greenhouse gas emissions due to forest fires. This research aims to assess the burnt area in tropical savanna forest cover type using medium resolution satellite imagery data by utilizing the Normalized Burn Ratio index in four villages in East Sumba Regency and estimating greenhouse gas emissions these activities. The results showed that the NBR method does not produce an estimate of the burned area with a fair degree of accuracy because the characteristic of channel 7 (SWIR) is sensitive to vegetation moisture content. The savanna forest cover type is the type of land cover identified as the most dominant burned area. It produces the highest greenhouse gas emissions compared to other land cover types.